Análises do modelo de educação ambiental aplicada na Escola de Rngen haria de Lorena da Universidade de Sao Paulo - Alves Prado, Andrés (2011)
Environmental education is itself an important way to disseminate knowledge for environmental conservation. This issue, however, presents some complexity. After all, it is not easy to spread it on a large scale with the practical implementation of its concepts. There are critical factors that go against the processes for environmental conservation, such as: the competitive pursuit of economic growth for countries, the use of unclean energy, and the promotion of the consumer society and capitalist interests among others. In this context, practical applications of environmental education become rather complex to implement. However, sustainable growth is something achievable provided that there is a concerted effort on the part of society, governments, industry and social organizations. Educational institutions at different levels can and should contribute in this process by using environmental education as the main tool and strategy for promoting environmental causes. The methodology of this study made use of literature and exploratory research to analyze the Escola de Engenharia de Lorena of Universidade de São Paulo